Contemporary Trade Governance and Cross-Border Data Flows: A Comparative Study of Sharīʿah Principles and International Legal Frameworks - Muhammad Azam; Naji Mohammad Alwreikat; Burhan Alsyouf; Abdel Salam Atwa Ali Al Fandi; Rawdah Abdul Karim Mohammad Pharaon (MILRev: Metro Islamic Law Review, 2026)
The rapid expansion of the digital economy has transformed international commerce, making cross-border data flows a crucial component of global trade governance. The increasing reliance on digital platforms, cloud computing, and data-driven services has generated legal challenges related to data privacy, cybersecurity, digital sovereignty, and regulatory fragmentation across jurisdictions. This study examines how contemporary legal frameworks regulate cross-border data governance and analyzes the tension between trade liberalization and regulatory control in digital trade systems. Using a qualitative doctrinal and comparative legal approach, the research evaluates the frameworks of the World Trade Organization (WTO), the European Union (EU), and major Indo-Pacific digital trade agreements. The analysis applies three criteria—legal enforceability, regulatory flexibility, and data protection intensity—to compare their approaches to digital trade governance and cross-border data flows. The findings reveal significant divergence among these frameworks, driven by differing regulatory philosophies and policy priorities. The WTO primarily emphasizes trade liberalization and non-discrimination, but lacks comprehensive mechanisms for data governance. In contrast, the EU adopts a rights-based model focused on robust data protection and regulatory oversight, while Indo-Pacific agreements favor flexible, market-oriented rules that facilitate data flows with limited restrictions. The study further finds that fragmentation in global digital governance is driven not only by regulatory differences but also by competing views of data as either an economic commodity or a protected legal right. The research concludes that effective global digital trade governance requires a harmonized framework balancing economic openness, data protection, cybersecurity, and national sovereignty. It proposes a principle-based harmonization model grounded in transparency, proportionality, interoperability, and regulatory accountability. Academically, this study contributes by developing a comparative analytical framework and by integrating Sharīʿah-based perspectives on ethical data governance, trust, and accountability into contemporary international debates on digital trade law.